Social experiences of children with disabilities in inclusive Portuguese preschool settings - Ferreira, M. (2017)
Based on peer sociometric reports, we examined how number of friendships, social acceptance, and characteristics of social networks vary as a function of disability profile. We also investigated teachers' awareness of the sociometric status of young children with disabilities. Participants were 86 children with disabilities (63 boys) enrolled in inclusive preschool classrooms of the Metropolitan Area of Lisbon, Portugal (M-age = 67.33 months, SD = 10.54). Findings suggest that children with severe or sociobehavioral disabilities may be at increased risk of social rejection and isolation, having fewer friends and lower social network centrality than children with mild disabilities. Low agreement between teachers' classifications of the social status of children with disabilities and classifications based on peer nominations raises concerns about their awareness of processes of social rejection and neglect. Findings highlight the need for interventions to support positive social experiences at the dyadic and group levels in Portuguese inclusive preschool classrooms.